PENGARUH INSENTIF DAN PENGEMBANGAN TERHADAP KINERJA KARYAWAN DI PDAM TIRTASARI BINJAI - Nur Augus Fahmi (Universitas Islam Islam Sumatera Utara, 2018)
This paper is based on the research regarding incentive and self-quality development of employees at PDAM Tirtasari Binjai. Both incentive and self-quality development is an important aspect to enhance the employees’ performance. Therefore, this research was conducted to know further more on how the incentive and self quality effect to the employees’s performance.The population of the research was all employees of the PDAM Tirtasari Binjai, and the number of them was 112 people. Random sampling technique was used to decide 88 employees as sample of the research. The questionnary and interview were used as instruments for data collection. The data that gained from the questionannary was processed through statistical approach and it would be cross-checked later with the data that obtained from interview. In this sense, the data from interview stands as complement and to support the statistical analysis. The result of the research indicated that the incentives (X1) had a significant impact to the employee’s performance (Y) as well as the self-quality development (X2) which wasa significant impact to the employees’ performance (Y).